The Effect of Cadmium Doping on Bscco Superconductors Prepared Via Coprecipitation Method - Abdulgader, Ali Agail Hamed (2004)
The coprecipitation technique was used in the preparation of cadmium doped Bi1.6Pb0.4Sr2Ca2Cu3O10 and Bi1.7Pb0.3Sr2Ca2Cu3O10 polycrystalline ceramic superconductors. In this study, the calcium site was subjected to Cd doping with nominal composition ranging from x=0 to x=0.1 at different sintering times. The superconducting properties of the samples have been investigated. The undoped samples, which exhibits TC(R=0) around 102 –104 K and TC-onset around 112-116 K, showed large flaky grains around 9-11 m in size which are randomly distributed. However, at longer sintering time (100 h) the undoped sample showed a better orientation as compared to that of the shorter sintering time (24 hr) sample. The calculated value of Josephson current, Io, obtained from the AC susceptibility data showed a much higher value (Io =100.04 A) as compared to the sample prepared by conventional method (Io =55.9 A). This indicates better grain connectivity and higher 2223 phase content, which was confirmed by SEM photographs. In addition, the nature of the ultra fine particles of the oxalate powders produced by coprecipitation method have increased the diffusion reaction and shortened the heat treatment procedure for the sample preparation, this leads to better superconducting properties as compared to the samples prepared by conventional solid state technique where its diffusion reaction requires high sintering temperatures for long duration and sometimes several grindings.